2011
DOI: 10.1179/2047773211y.0000000010
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of triple drug administration (TDA) with praziquantel, ivermectin and albendazole for the prevention of neglected tropical diseases in Nigeria

Abstract: Onchocerciasis, lymphatic filariasis (LF), schistosomiasis and soil transmitted, helminthiasis (STH) are all coendemic in Nigeria. Annual mass drug administration (MDA) with ivermectin (for onchocerciasis), albendazole (for STH and with ivermectin for LF) and praziquantel (for schistosomiasis) is the WHO-recommended treatment strategy for preventive chemotherapy. Separate delivery rounds for distribution of these drugs have been the usual approach to MDA. All three drugs, however, have now been shown to be cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 10 publications
1
57
1
Order By: Relevance
“…These drugs have demonstrated varying egg reduction and curative rates (Table 3). There are increasing reports of mass deworming programme across the country [69,109,110], and studies have suggested that sustainable decrease in infection burden is a result of continuous use of antihelminthics [69,78].…”
Section: Control Effortsmentioning
confidence: 99%
“…These drugs have demonstrated varying egg reduction and curative rates (Table 3). There are increasing reports of mass deworming programme across the country [69,109,110], and studies have suggested that sustainable decrease in infection burden is a result of continuous use of antihelminthics [69,78].…”
Section: Control Effortsmentioning
confidence: 99%
“…Four studies evaluated the cost-effectiveness of interventions for several NTDs, showing the benefits of combined strategies (Leslie et al, 2011;Evans et al, 2011;Guyatt et al, 2001;Ndeffo Mbah et al, 2013a). All of these studies focussed on African countries; two evaluated real programmes (Leslie et al, 2011;Evans et al, 2011); one modelled the impact on transmission (Ndeffo Mbah et al, 2013b) and one evaluated the effect of deworming on anaemia (Guyatt et al, 2001).…”
Section: Multiple Ntdsmentioning
confidence: 99%
“…All of these studies focussed on African countries; two evaluated real programmes (Leslie et al, 2011;Evans et al, 2011); one modelled the impact on transmission (Ndeffo Mbah et al, 2013b) and one evaluated the effect of deworming on anaemia (Guyatt et al, 2001). One evaluated the cost-savings when switching from the separate delivery of three drugs for onchocerciasis, lymphatic filariasis, schistosomiasis and STH MDA to coadministration of the drugs (triple drug administration), which was found to be clinically safe (Evans et al, 2011). Another evaluated programme costs for schistosomiasis and STH control in Niger; cost-effectiveness was evaluated between the start of the intervention (baseline) and the follow-up period (2 years) across eight schools and four communities (Leslie et al, 2011).…”
Section: Multiple Ntdsmentioning
confidence: 99%
“…Here, it should also be noted that surveillance of schistosomiasis and STH does not operate alone and for it is, or should be, incorporated within the geographical landscape for surveillance of other NTDs, for example for lymphatic filariasis and onchoceriasis [29,45]. This is because for PC treatment associated with the latter two diseases, impacts upon STH, for IVM and ALB taken individually or combined, has tangible impact upon each nematode species [46]. Indeed, the algorithm for PC is illustrated in Figure 2, in which umbrella treatment decisions for lymphatic filariasis and onchocerciasis are part of the treatment decisions tree.…”
Section: ■ Rationale Drug Delivery Across a Disease Landscapementioning
confidence: 99%